La república del orden: Simón Bolivar, Andrés Bello y las transformaciones del pensamiento político de la Independencia - Jaksic, Iván (Historia, 2003)
This essay explores the relationship between Andrés Bello and Simón Bolívar, arguing that their history of friendship and misunderstandings had a profound impact on Bello’s decision to come to Chile. It is furthermore argued that Bello would have avoided any references to Bolívar had it not been for the allegations, aired in the press, that he had betrayed the Libertador. However, in the process of responding to the accusations, he conveyed a view of Bolívar that fit well with his own desire to promote the rule of law in Chile and beyond. It is not coincidental, then, that he transmitted highly negative views of Bolívar at the same time that he was about to launch the Civil Code. The essay concludes by suggesting that Bolívar and Bello represent two different perspectives on post-independence republicanism, one informed by classical sources, and the other drawing on emerging liberal views on the centrality of civil legislation for the consolidation of the new order in the continent.